Inhibition of Rho GEFs attenuates pulmonary fibrosis through suppressing myofibroblast activation and reprogramming profibrotic macrophages - Chengju Luo; Chenqi Huang; Yuqi Zhu; Yuxin Zhou; Yansheng Qiao; Chenxiao Shi; Yuan Gao; Yongjian Guo; Libin Wei (Cell Death and Disease)
Abstract Idiopathic pulmonary fibrosis has a poor prognosis, with existing medications only partially alleviating symptoms, highlighting the urgent need for new therapeutic approaches. The dysregulations of Rho GTPases/ROCK are related with various diseases, including fibrosis. Nevertheless, the development of drugs for pulmonary fibrosis treatment has predominantly concentrated on ROCK inhibitors. Small GTPases have been historically recognized as “undruggable”. Here, we explore a novel Rho GEFs inhibitor GL-V9, and find that GL-V9 alleviates bleomycin-induced pulmonary fibrosis in mice by inhibiting myofibroblast activation and reprogramming profibrotic macrophages. Distinct from the mechanisms of the first-line drug Nintedanib, GL-V9 binds to the DH/PH domain of Rho GEFs and block the activation of Rho GTPase signaling. This action subsequently suppresses myofibroblast activation by interfering with Rho GTPase-dependent cytoskeletal reorganization and the activity of MRTF and YAP, and inhibits M2 macrophage polarization by modulating RhoA/STAT3 activity. The discovery of new regulatory mechanisms of GL-V9 suggests that targeting Rho GEFs represents a potent strategy for pulmonary fibrosis treatment.